Analisis Tingkat Kemampuan Vo2 Max Atlet Renang Putra Raflesia Swimming Klub Kota Bengkulu - Brian, Brian; Mariska, Mariska; Apriansyah, Dolly (Educative Sportive, 2024)
this study aims to determine the level of Vo2 Max ability of Male Athletes of Raflesia Swimming Club Bengkulu City. This research method is descriptive research. The research sample amounted to 23 people. The instrument used in this research is the Bleep Test/Multi-Stage. Where the results of research and discussion, the researcher concluded that the VO2 Max ability performed by male athletes of Raflesia Swimming Club Bengkulu City performed by 13 men in the sufficient category, namely as many as 7 men or with a percentage of 54%. Then for the VO2 Max ability carried out by male athletes of Raflesia Swimming Club Bengkulu City conducted by 10 girls in the sufficient category, namely as many as 6 girls or with a percentage of 60%.From the results of the research obtained by the results of the VO2 Max ability test conducted by the overall male athletes of Raflesia Swimming Club Bengkulu City conducted by 13 boys and 10 girls in the sufficient category, namely as many as 13 people or with a percentage of 57%.